Working Together: Critical Perspectives on Six Cross-Sector Partnerships in Southern Africa - Rein, Melanie (Journal of business ethics, 2009)
This paper examines six cross-sector partnerships in South Africa and Zambia. These partnerships were part of a research study undertaken between 2003 and 2005 and were selected because of their potential to contribute to poverty reduction in their respective countries. This paper examines the context in which the partnerships were established, their governance and accountability mechanisms and the engagement and participation of the partners and the intended beneficiaries in the partnerships. We argue that a partnership approach which has proven successful in one context can be used as a valuable learning resource. However, a partnership’s work, which includes all aspects of the partnership and its activities, cannot necessarily be transferred directly to another partnership without a thorough and locally informed analysis of the context in which it is implemented. In addition, we suggest that it is difficult to assess whether the good intentions behind partnerships were translated into real benefits for target groups as effective monitoring and evaluation procedures were not in place in the partnerships studied. Similarly, the absence of regularised governance and accountability systems in partnerships made it difficult to support partner and beneficiary participation and engagement. We conclude that there is a need to move beyond a ‘one-size-fits-all’ approach to partnerships and that partnership replication should focus more strongly on the transfer of learning about partnership processes instead of simply copying partnership activities. Moreover, the development of stronger mechanisms for assessing and ensuring accountability towards both partners and intended beneficiaries is required if partnerships are to meet their intended objectives.